POLICE DISCRETION IN INVESTIGATION OF TRAFFIC AFFECTS PERFORMED BY CHILD - Leni Dwi Nurmala; Robby Waluyo Amu; Yusrianto Kadir (Geuthèë Institute, Aceh, 2022)
The implementation of discretion by the police seems to be against the law, but it is a way out that is indeed given by law to the police in order to provide efficiency and effectiveness for the greater public interest, furthermore discretion should not be eliminated. Discretion cannot be removed and should not be eliminated. Discretion is an integral part of the role of the institution or organization. However, discretion can be limited and controlled, for example by tightening written orders and the existence of programmed decisions that are at least able to formulate and demand discretionary action. The problem is, unprogrammed decisions often appear and open the door wide for discretionary making. That the mechanism for applying police discretion to traffic crimes committed by children at the Police investigation level is that the traffic police visited the scene of the case and then sketched the scene of the case, helped victims, recorded witnesses, secured evidence of accidents such as vehicles, driver's licenses, and STNK, for a further investigation process, After that an investigation is carried out by the police to make a case analysis and discretion is carried out if the accident that occurs is minor and the perpetrator is a child who causes a minor accident and a single accident that can be resolved with material compensation, then an agreement is made between the two parties for solving traffic accident cases.